Hubungan Asupan Zat Besi, Protein dan Kebiasaan Melewatkan Makan dengan Kejadian Anemia pada Remaja Putri di SMP Negeri 16 Samarinda - Awalinda, Sri Shinta; Safika, Erri Larene; Wahyuni, Leny Eka Tyas; Ismail , Ismail; Afiah, Nurul (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2025)
Anemia was a condition characterized by a small number of red blood cells and was commonly experienced by adolescent girls due to menstruation and increased nutritional needs during growth. In 2023, the highest number of anemia cases in the working area of Puskesmas Loa Bakung, Samarinda, was found among female students of SMP Negeri 16 Samarinda, with a prevalence of 25% out of 190 cases. The purpose of this study was to analyze the association between iron intake, protein intake, and the habit of skipping meals with the incidence of anemia among female students at SMP Negeri 16 Samarinda. A cross-sectional design was used for this study. As much as 72 respondents were selected with purposive sampling. Data for this study was collected through haemoglobin (Hb) testing, interviews using the SQ-FFQ questionnaire and a meal-skipping questionnaire. A total of 37 (51.4%) female students suffered from anemia, 56 (77.8%) female students consumed adequate protein intake, and 67 (93.1%) female students had insufficient daily iron intake. As much as 55 (76.4%) female students did not regularly eat breakfast. Statistical analysis showed a significant relationship between iron intake (p=0.023), protein intake (p=0.010), and the habit of skipping breakfast (p=0.038) with anemia. However, this study didn’t find any association between skipping lunch (p=0.207) or dinner (p=0.658) with anemia. It was necessary to raise awareness among adolescent girls about the importance of breakfast and consuming nutritious foods, especially those rich in iron and protein to prevent anemia and support healthy development during adolescence.